2019
DOI: 10.18559/ebr.2019.1.5
|View full text |Cite
|
Sign up to set email alerts
|

A disequilibrium mechanism: When managerial decisions cause macroeconomic instability

Abstract: The paper aims to develop our understanding of the processes and mechanisms leading to economic instability. The research design and methods: the paper employs a simple game-theoretic model aimed at depicting why the mechanism connecting nonmaterial motivation of managers and the propensity of economic systems is unstable. The findings are as follows: managers, driven by the nonmaterial value of work, choose strategies that maximize the likelihood of prolonging their employment. Shortsighted CEOs may prefer st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…The third problem is moral hazard: the agent has an incentive not only to perform the agreed task, but also to act in an unacceptable way through undue effort put into a venture (Rasmussen, Gulbrandsen, 2012). Maziarz (2019) proposes to add also tacit factors to moral hazard explanation. In light of the relationship between the entrepreneur and the investor, it can be concluded that the conflict of goals may result from the fact that the goal of the lender is to maximize the return on investment, and the entrepreneur's goal may be to minimize efforts.…”
Section: Moral Hazard In Theoretical Explanation Of Financial Constrainsmentioning
confidence: 99%
“…The third problem is moral hazard: the agent has an incentive not only to perform the agreed task, but also to act in an unacceptable way through undue effort put into a venture (Rasmussen, Gulbrandsen, 2012). Maziarz (2019) proposes to add also tacit factors to moral hazard explanation. In light of the relationship between the entrepreneur and the investor, it can be concluded that the conflict of goals may result from the fact that the goal of the lender is to maximize the return on investment, and the entrepreneur's goal may be to minimize efforts.…”
Section: Moral Hazard In Theoretical Explanation Of Financial Constrainsmentioning
confidence: 99%